Inequality and democracy - Anna Soci (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2019)
The paper is about the political consequences of increasing economic inequality in Western economies. Political theorists have often stressed that democracy is in troubles when its population is not broadly uniform in income and wealth because unequal economic resources can easily translate into a surplus of political resources in the hands of the few. The connections between economic inequality and democracy, however, are not easy to detect and the body of literature is not so large to provide robust assessments of their complex relationship. The aim of this paper is to review the links between the two and to offer some hints on the political relevance of the inequality consequences, if any, on democracy.
Keywords: A13; D6; 330; Inequality; Social consequences; Political consequences; Democracy change